The Public Perception About Agroforestri in The Village Sumberejo Poncokusumo Malang - Adi Suryo Purnomo; Saimul Laili; Hasan Zayadi (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
The affected agricultural land from the rate of conversion is approximately 100,000 ha / year, while 40,000 ha / year of new agricultural land can be printed by the government. Population growth, land tenure by farmers has diminished in size. The area of ​​land ownership in 2012, per farmer is approximately 0.22 ha. It is estimated that it will decrease by 0.18 ha in 2050. This condition makes farmers' welfare decreases due to the inefficient land for farming. The research was conducted on 28 January - 28 February 2019 in 2 locations, Jajang Hamlet and Wonokerto Hamlet which were included in Sumberejo Village, Sumberejo Village at 980 meters above sea level. Sumberejo Village is one of the villages included in the Poncokusumo District, Malang Regency. The data obtained in the form of images were obtained through direct observation at the location of the study. From the exploration carried out found 27 types of supporting plants (shade and interlude) consisting of trees and other commodity crops. In this case the problem of the Sumberejo village plantation community from the one we interviewed directly complained about the lack of knowledge about plants suitable for agroforestry and knowledge about hatcheries and buffer plants. Based on the value of the perceptions of the percentage of Wonokerto and Jajang Hamlet communities the highest score was 93% related to the mixed cropping system problem, while the lowest percentage value was found in the knowledge about 79% in Jajang Hamlet and 80% in the Wonokerto Hamlet perception.